KEDUDUKAN PSIKOLOGI FORENSIK DALAM PENANGANAN PELAKU TINDAK PIDANA PEMBUNUHAN DENGAN KEKERASAN TERHADAP ANAK - Anis Sulmustakim (Universitas 17 Agustus 1945 Samarinda, 2019)
ABSTRACT The position of Forensic Physology in the presentation is very close to obtaining a decision or determination in the investigation of a criminal offense carried out by the perpetrator, it is very important to know the psyche of the perpetrator and how to handle it in the investigation. From this background can be raised several problems, namely: How is the position of psychological Forensi to find out the cause of the perpetrators of murder with violence against children and How to deal with the perpetrators of murder with violence against children if the perpetrators can win the responsibility and cannot answer their actions. The discussion of these problems requires an approach method, specification of research types and sources of data, data collection methods and data analysis methods, from which the conclusions can be obtained as follows: very active role in forensic psychology in investigating perpetrators with investigators so that investigators can decide or report on the psychiatric results of the perpetrator to strengthen in the trial whether the suspect can bear the responsibility or not and the mechanism of investigation, sending SPDP, forced efforts, examinations, title cases, settlement of case files to the public prosecutor, surrender of suspects and evidence, and termination of investigation who plays with cannot bear the responsibility, namely the examination of a psychologist or psychiatrist, Sp3 dismissal before a court decision Keywords: Forensic Physics, Handling in Investigation, Psychology of Actors